A DESCRIPTION OF THE CHARACTERISTICS OF HEPATIC CIRRHOSIS PATIENT IN ABDUL WAHAB SJAHRANIE REGIONAL PUBLIC HOSPITAL SAMARINDA - Tri Wulandari Wulandari; Nirapambudi Devianto; Fransiska A. Sihotang (Universitas Muhammadiyah Kalimantan Timur, 2020)
Hepatic cirrhosis is a late stage liver disease characterized by the replacement of normal hepatocyte cells with fibrosis tissue. The severity of hepatic cirrhosis can be determined using Child-Pugh criteria which are divided into Grades A, B and C. This study aimed to find out the characteristics of hepatic cirrhosis patients in Abdul Wahab Sjahranie Regional Public Hospital in Samarinda. The design of this study was descriptive observational. Participants in this study consisted of 58 hepatic cirrhosis patients who were hospitalized in Abdul Wahab Sjahranie Regional Public Hospital in Samarinda from June 2017 to June 2018. Variables in this study were age, gender, period of stay, conditions at discharge, and the severity of cirrhosis. The researchers used data from medical records of cirrhosis patients. From 58 participants in this study, they were mostly people in the age of 46-55 years (43.1%) and the majority were male (70.7%).The maximum period of stay in hospital was less than 1 week (58.6%) and the condition when they went back home were mostly with outpatient treatment (79.3%). The severe degree of cirrhosis that was found was Child-Pugh C (63.8%).